DETECTION OF PLANT LEAVES DISEASE USING MACHINE LEARNING APPROACH - m.Bhavya Sri, b.Sridhara Murthy (International Journal of Advanced Science and Technology, 2020)
Agriculture is a fundamental cause of living. Agriculture gives work possibilities for village people on a big scale in an originating nation like India. the plant leaves are necessary for the fast-growing plants and to improve the composition of gatherings. When different diseases within their leaves attack plants, that will consequence in the product of agriculture and valuable loss—also, the decrease in both the quality and amount of agricultural composition. It is also difficult for farmers to classify diseases in the leaves of plants. Farmers are currently spraying pesticides on plants, but this leads to people being immediate or spread through health or possibly financially. To identify these plant diseases, various fast techniques need to choose. In this paper, we suggest a fantasy-based automatic detection of plant disease detection using the Image Processing Technique. Image processing algorithms developed to identify the plant disease or attack by identifying the color feature of the leaf area. K-mean clustering algorithm is used for color segmentation, and GLCM is used for feature extraction and finally at the classification Modified Random Forest (MRF) algorithm used. The experimental results shows that the recommended system performs better classification accuracy of 86% applying GLCM features.